FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT ADOPSI PETANI PADA TEKNOLOGI BUDIDAYA PADI SAWAH SISTEM LEGOWO DI KELURAHAN DUSUN BESAR KECAMATAN GADING CEMPAKA KOTA BENGKULU - Utama, Satria Putra; Cahyadinata, Indra; Junaria, Rahmad (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2007)
The study aimed at identification the factors that connected with the level of farmer’s adoption toward the rice field’s technology in legowo system in Dusun Besar, Gading Cempaka subdistrict Bengkulu town were level education, age, the wider of farm, experience, motivation, activity of the farmer in counseling, farmer’s conception about legowo system and farmer’s cosmopolittness. The study was conducted in Dusun Besar, Gading Cempaka subdistrict Bengkulu town. Total samples were 40 farmers and data collection was observation method, documentation method and method of questionaire. Data were analyzed using Statistic non parametric that is correlation test of rank spearman. The result of this research showed that the level of farmer’s adoption toward technology in legowo system in Kelurahan Dusun Besar, Gading Cempaka subdistrict, Bengkulu Town were high. And also there were correlation between the factor of the level education, motivation, activity of the farmer in counseling, farmer’s conception about legowo system with the level of farmer adoption toward rice field’s technology in legowo system. In otherwise, there was no correlation between age, the wider of farm, experience, and farmer’s cosmopolittness with the level farmer adaption toward the rice field’s technology in legowo system.